2022
DOI: 10.1371/journal.pntd.0010449
|View full text |Cite
|
Sign up to set email alerts
|

Porcine model of neurocysticercosis by intracarotid injection of Taenia solium oncospheres: Dose assessment, infection outcomes and serological responses

Abstract: Background Neurocysticercosis (NCC) is the infection of the human central nervous system (CNS) by Taenia solium larvae that cause significant neurological morbidity. Studies on NCC pathophysiology, host-parasite interactions or therapeutic agents are limited by the lack of suitable animal models. We have previously reported that carotid injection of activated T. solium oncospheres directs parasites into the CNS and consistently reproduces NCC. This study assessed the minimal dose required to consistently obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…In general, antigen profiles during the follow-up of pigs experimentally infected with T. solium were very similar between assays. We observed high antigen levels in all pigs with viable cysticercosis at day 28 PI and onward, similar to previous studies reported in the literature [ 24 , 30 , 31 ]. Equally, the profile of antigen dynamic in pigs without cysticercosis infection or with only degenerated cysts also showed a similar trend between assays.…”
Section: Discussionsupporting
confidence: 91%
“…In general, antigen profiles during the follow-up of pigs experimentally infected with T. solium were very similar between assays. We observed high antigen levels in all pigs with viable cysticercosis at day 28 PI and onward, similar to previous studies reported in the literature [ 24 , 30 , 31 ]. Equally, the profile of antigen dynamic in pigs without cysticercosis infection or with only degenerated cysts also showed a similar trend between assays.…”
Section: Discussionsupporting
confidence: 91%
“…In general, antigen pro les during the follow-up of pigs experimentally infected with T. solium were very similar between assays. We observed high antigen levels in all pigs with viable cysticercosis at day 28 PI and onwards, similar to previous studies reported in the literature [24,29,30]. Equally, the pro le of antigen dynamic in pigs without cysticercosis infection or with only degenerated cysts also showed a similar trend between assays.…”
Section: Discussionsupporting
confidence: 90%
“… 63 Recently, Arroyo et al 72 reported on a porcine model in which activated T. solium eggs were administered directly into the common carotid artery, resulting in a more than 66.6% success rate of CNS cyst infection with parasitic loads that resemble that of human NCC. 73 Although this represents a powerful new model system, it is worth noting that it is possible that some aspect of pathology in NCC results from the mismatch between the natural evolution of Taenia larvae to reside in pig tissue and their accidental occurrence in the human brain.…”
Section: Recent Advances In Modeling Nccmentioning
confidence: 99%